8-3x+10=9

Simple and best practice solution for 8-3x+10=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-3x+10=9 equation:



8-3x+10=9
We move all terms to the left:
8-3x+10-(9)=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3

See similar equations:

| 18-3=4x+2 | | t+4=-15 | | -5(-7n-5)=-7+3n | | 36x3–256x=0 | | 7+3m=- | | 4x+2=18x-3 | | x÷9=12 | | q+14=8(q) | | 6(5n+5)=7n+7 | | 18x-36=-36 | | 16.5-6.5k=-7(5.5k+6) | | n-3-2n=(-6) | | 4-3x=8+3x | | 3x^2+54x=-255 | | 43=-x/7 | | Y=8x^2-288 | | 6t-12=24-2t | | 4-3x=8x3x | | -v/6=-47 | | -12=4(x-6) | | 20=x/20 | | -3x+8=-2+9x | | x/4-16=10 | | -11y-6=11-8y | | 4(-x+1)+3=-2(x+1) | | 5w+15=105 | | -11y-6=2-8y | | 15x+2=10x+23 | | (2)1-x=5 | | -5(8n+6)=36+7n | | -92=-8+2(6x+6) | | (4)1-x=5 |

Equations solver categories